Anaplastic Thyroid Carcinoma: Current Treatments and Potential New Therapeutic Options with Emphasis on TfR1/CD71 - Rosalba Parenti; Lucia Salvatorelli; Gaetano Magro (International Journal of Endocrinology)
Anaplastic thyroid carcinoma (ATC) is one of the most aggressive human cancers. Actually, ATC is refractory to conventional therapies, including surgery, chemotherapy, radiotherapy, and radioiodine (131I) therapy. Accordingly, genetic and molecular characterizations of ATC have been frequently and periodically reviewed in order to identify potential biological markers exploitable for target therapy. This review briefly focuses on main molecular events that characterize ATC and provides an update about preclinical studies. In addition, the overexpression of transferrin receptor 1 (TfR1/CD71) by neoplastic cells of ATC is emphasized in that it could represent a potential therapeutic target. In this regard, new therapeutic approaches based on the use of monoclonal or recombinant antibodies, or transferrin-gallium-TfR1/CD71 molecular complexes, or lastly small interfering RNAs (siRNAs) are proposed.